Implementation Analysis of Fast Track and Variable Work Overtime on Delays in the Building Construction Project - Pasca Fitri Febriani; Rizal Bahaswan; Julistyana Tistogondo (The Spirit of Society Journal: International Journal of Society Development and Engagement)
In the implementation of construction projects, complex challenges are often faced, one of which is project delays. This research aims to analyze the application of the Fast Track Construction (FTC) method based on time variables in the delay of the SII Office Surabaya building construction project. This research uses a quantitative method by collecting secondary data from the project contractor. The analysis was conducted on the remaining structural and architectural work using the Critical Path Method (CPM) and Microsoft Project. The research results show that of the three acceleration analyses with the FTC 50% method, 4 hours/day overtime and 6 hours/day overtime, the most effective and efficient application is with 4 hours/day overtime. With the addition of overtime, it is known that the more overtime is added, the less it reduces the duration of work items but can reduce the indirect costs of the project. And based on the results of statistical analysis using the Paired T Test, it was found that Ha was accepted and Ho was rejected, which means that the data is significant.